2013
DOI: 10.1111/add.12079
|View full text |Cite
|
Sign up to set email alerts
|

Prospective correlates of drinking cessation: variation across the life‐course

Abstract: Aims To assess age variation in correlates of drinking cessation. Design Prospective study of a U.S. general population sample. Setting Face-to-face household interviews. Participants Past-year ≥monthly drinkers interviewed at baseline and 3-year follow-up (n=14,885). Measurements Baseline values and selected changes over follow-up in alcohol consumption, alcohol use disorder (AUD), sociodemographic and health characteristics, other substance use and psychiatric comorbidity were used to predict drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 53 publications
(77 reference statements)
2
45
0
Order By: Relevance
“…Of these, five were among patients in SUD treatment- 4246 of which two targeted adolescents, 43,44 four were among participants delivered smoking cessation interventions, 29,38,41,47 of which one study targeted adolescents during psychiatric hospitalization, 29 and two were among adult general population samples. 39,40 (Figure 2)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, five were among patients in SUD treatment- 4246 of which two targeted adolescents, 43,44 four were among participants delivered smoking cessation interventions, 29,38,41,47 of which one study targeted adolescents during psychiatric hospitalization, 29 and two were among adult general population samples. 39,40 (Figure 2)…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 studies with positive findings, eight (73%) found improved alcohol-specific outcomes of fewer drinks per day, 38 fewer drinks per week, 47 decreased likelihood of relapse, 43 increased abstinence for 12 months 40,42 and for 30 days, 45 increased likelihood of “alcohol-abstainer” trajectory membership, 44 and decreased likelihood of being diagnosed with alcohol use disorder. 39 Five studies (45%) reported drug-specific outcomes or general “drug” outcomes that excluded alcohol; one found increased likelihood of past year abstinence from drugs, 42 one found decreased likelihood of being diagnosed with a drug use disorder, 39 two found improved marijuana-specific outcomes of reduced percent of using days 47 and decreased likelihood of relapse and longer time to relapse 43 and one found reduced stimulant craving.…”
Section: Resultsmentioning
confidence: 99%
“…Wave 1 factors predicting Wave 2 drinking cessation: absence of comorbidity [258], [259] recent childbearing, lower drinking amounts; and non-white race/ethnicity [259]. Among those with Wave 1 alcohol dependence, factors predicting Wave 2 abstinent recovery (no drinking or symptoms) were minority race/ethnicity, having young children, religious involvement, and treatment/12-step participation [260].…”
Section: Major Findingsmentioning
confidence: 99%
“…While a variety of studies have attempted to answer these questions, the findings have not been consistent. Older studies suggest that smoking cessation results in an increase in alcohol use [911], while more recent epidemiologic studies have found that alcohol use decreases [1216] and other studies have found that alcohol use does not change [17–22] as a result of smoking cessation. Most recently, Lisha et al [23] found that alcohol use did not change with smoking cessation; however this study used 90-day recall methods for substance use and the populations studied were either alcohol dependent patients in early recovery or HIV positive patients, representing specific subsets of the general population.…”
Section: Introductionmentioning
confidence: 99%